Consumption of Chokeberry Bio-Products Improves Specific Metabolic Parameters and Increases the Plasma Antioxidant Status - Ewa Olechno; Anna Puścion-Jakubik; Katarzyna Socha; Caterina Pipino; Małgorzata Elżbieta Zujko (MDPI AG, 2024)
Because of its high antioxidant activity, chokeberry can be used both in the prevention and treatment of various metabolic disorders. In this study, for the first time, the synergistic effects of chokeberry juice and chokeberry fiber on selected metabolic and anthropometric parameters were assessed during a 90-day intervention including 102 people (67 women and 35 men). After 60 days of intervention with chokeberry juice, statistically significant increases in the muscle mass and antioxidant potential of the serum were observed. In turn, there were decreases in the waist circumference, systolic blood pressure, diastolic blood pressure, heart rate, glycated hemoglobin, glucose, LDL cholesterol, eGFR, and ALT level. The addition of chokeberry fiber for the next 30 days resulted in stabilizations of the diastolic blood pressure, glycated hemoglobin, glucose, and waist circumference, as well as reductions in the values of the heart rate, LDL cholesterol, insulin, and AST level. After 90 days, a significant increase in the FRAP value was also observed. This intervention indicates that chokeberry products may have a beneficial effect on metabolic health and serve as a foundation for developing functional foods.